The Economic Significance of Equity Capital: Lessons from Venture Investing by an Economist-Practitioner - William H. Janeway (Levy Economics Institute of Bard College, 1991)
I was motivated to address this subject by the rich irony of last year's Nobel Prize in Economics. The end of the LBO era was crowned by the recognition of work which purported to demonstrate that the value of an enterprise is independent of the volume of its debt. In response, this paper is an attempt to inform the post-Keynesian critique of Modigliani-Miller with the experience of one whose profession it is to invest equity capital in Imperfect markets under conditions of uncertainty. The "regulation and intervention" with which I am professionally concerned is that of a proprietary venture investor, prepared to forego liquidity and to accept strategic responsibility for the performance of the enterprises we control. I have principally drawn on Douglas Vickers' discussion of the nature and role of "money capital" beyond the General Equilibrium domain where the issues of finance are, alternatively, oxymoronic or redundant. I can testify that Vickers' examination of the "full marginal cost of relaxing the money capital availability constraint" integrates the analysis of operating and financial issues under real world conditions'. Vickers and like-minded analysts such as Marris, Herendeen and Chamberlain have succeeded, I judge, in establishing the economic role of equity capital in an uncertain world. From that analysis and my own experience, the injunction to maximize growth subject to (1) delivering minimally satisfactory rates of return on sales and on capital employed while (2) not risking the long-run survival of the frn makes operating and investment sense.
Keywords: 330